THE OBSTACLE OF GERAKAN LITERASI SEKOLAH IN ELEMENTARY SCHOOL: A PHENOMENOLOGY STUDY - Ifan Awanda (El Midad, 2025)
This study discusses the phenomenological obstacles to implementing the Gerakan Literasi Sekolah (GLS) in Elementary Schools. Problems in this research stem from the lack of focus on promoting literacy and fostering a love for reading and writing, especially for children at the school base. The purpose of the phenomenological studies on constraints in the implementation of the Gerakan Literasi Sekolah (GLS) is to analyze the experiences of those involved in teaching literacy, revealing the specific challenges and obstacles they face in implementing the Gerakan Literasi Sekolah (GLS). This study uses a phenomenological approach and uses in-depth interviews and observations. The results of the research are: 1) the existence of obstacles? in general terms mentioned by teachers or educators, including a lack of training for teachers, 2) the implementation of GLS, primarily in Elementary Schools, has not yet been achieved to the maximum because of various factors that become inhibitors in it. 3) One of them lacks training in integrating technology into teaching, as well as limited access to important sources of power, such as software and devices, and doubts about the utility of learning-based games in increasing academic achievement.